2001
DOI: 10.1038/35065091
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the neuronal glutamate transporter EAAT4 by two interacting proteins

Abstract: Glutamate is the main excitatory neurotransmitter in the mammalian central nervous system and is removed from the synaptic cleft by sodium-dependent glutamate transporters. To date, five distinct glutamate transporters have been cloned from animal and human tissue: GLAST (EAAT1), GLT-1 (EAAT2), EAAC1 (EAAT3), EAAT4, and EAAT5 (refs 1-5). GLAST and GLT-1 are localized primarily in astrocytes, whereas EAAC1 (refs 8, 9), EAAT4 (refs 9-11) and EAAT5 (ref 5) are neuronal. Studies of EAAT4 and EAAC1 indicate an extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
201
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(209 citation statements)
references
References 26 publications
8
201
0
Order By: Relevance
“…Intriguingly, in rat, overexpression of the ortholog induces the reorganization of the actin cytoskeleton and the formation of membrane ruffling. 23 The SNP rs9864101, whose effect on IA was modified by gender, is located in the gene IQSEC1. ARF-GEP100 protein (ADP-ribosylation factorguanine nucleotide-exchange protein-100 kDa) encoded by this gene activates ADP-ribosylation factor protein, ARF6, and regulates cell adhesion through recycling E-cadherin and remodeling actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, in rat, overexpression of the ortholog induces the reorganization of the actin cytoskeleton and the formation of membrane ruffling. 23 The SNP rs9864101, whose effect on IA was modified by gender, is located in the gene IQSEC1. ARF-GEP100 protein (ADP-ribosylation factorguanine nucleotide-exchange protein-100 kDa) encoded by this gene activates ADP-ribosylation factor protein, ARF6, and regulates cell adhesion through recycling E-cadherin and remodeling actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies have also shown that glutamate transporter expression and activity may be regulated by different endogenous or exogenous factors [6,8,10,13,15,27,31,35,44,48,53], we are now studying the possible role of physiological stimuli, such as PKC activation, or oxidative stress on glutamate transporter activation/inactivation or translocation in platelets. The final goal of these studies is the possibility of using platelets as peripheral model to investigate the role of glutamate, its transporters and its effect pathway in neurodegenerative disorders, with the clear advantage of being easy to obtain, suitable for pharmacological and clinical studies and, compared to human brain tissue studies, of being independent from postmortem or end-stage changes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recent work suggests that wild-type -III-spectrin, but not SCA5 mutant spectrin, can stabilize the glutamate transporter EAAT4 at the cell membrane (Jackson et al, 2001;Ikeda et al, 2006). Consistent with possible dominant-negative effects, expression of the SCA5 mutant proteins results in reduced numbers of synaptic boutons at synaptic termini.…”
Section: Sca5 Mutations Cause Synaptic Deficitsmentioning
confidence: 84%
“…First, wild-type but not mutant -III-spectrin stabilizes the Purkinje cellspecific excitatory amino acid transporter 4 (EAAT4) at the surface of the plasma membrane (Ikeda et al, 2006). In addition, cell fractionation studies have shown differences in the localization of EAAT4 and the glutamate receptor delta 2 subunit (GluR2) in cerebellar synaptosomal fractions from SCA5 versus control autopsy tissue (Ikeda et al, 2006), and the C-terminal domains of GluR2 and EAAT4 have been shown to physically interact with spectrin (Hirai and Matsuda, 1999;Jackson et al, 2001). Finally, -III-spectrin is a Golgi-and vesicle-associated protein that interacts with dynactin (Holleran et al, 2001).…”
Section: Introductionmentioning
confidence: 99%